Seroprevalence to adeno‐associated virus type 6 in people with hemophilia B from a UK adult cohort. Issue 4 (3rd June 2022) - Boyce, Sara; James, Izabela; Rangarajan, Savita; Curry, Nicola; Bagot, Catherine; Austin, Steven; Laffan, Mike; Mangles, Sarah; Chandrakumaran, Kandiah; Mundy, Carina
Abstract: Background: Gene therapy shows promise as a potential "cure" for hemophilia A and B. Adeno‐associated virus (AAV) vectors are the leading platform to deliver modified genetic code of factor VIII or IX to the liver effecting endogenous production. Patient exposure to wild‐type AAV leads to the formation of neutralizing factors, which can prevent successful transduction. It is thus important to establish the seroprevalence of the AAV serotypes in people with hemophilia to aid prediction of successful gene transfer. The seroprevalence of AAV6 in UK people with hemophilia B is not yet reported. Objectives: We studied the prevalence of anti‐AAV6 neutralizing factors in UK people with hemophilia B ( n = 49). We collected data on people's hepatitis C exposure and treatment with plasma‐derived factor IX (FIX) to identify if there was correlation with AAV6 exposure. Methods: Serum samples and patient data were collected from 49 people with hemophilia B registered at UK hemophilia comprehensive care centers. The samples were tested for neutralizing factors to AAV6 using a cell‐based transduction inhibition assay. Results: Thirty‐one percent of patients had serum neutralization against AAV6. There was no correlation between AAV6 seropositivity and previous treatment with plasma‐derived FIX products or hepatitis C exposure. Conclusion: Based on limited data, there is no evidence of association between the presence of AAV6 neutralizing factors in people with hemophilia B and exposure to contaminated plasma derivatives. The frequency of AAV6 neutralizing factors in our hemophilia B cohort is similar to UK people with hemophilia A and non‐hemophilia populations.